A Rare Nasopharyngeal Carcinoma'S Metastasis To The Ear - Shea Ann Wee; Nour Hanan Daniah; Ahmad Anwaar; Azreen Zaira Abu Bakar; Shahrul Hitam; Noorjehan Omar; Nor Azirah Salahuddin; Siti Asmat Md Arepen; Zubaidah Hamid; Nor Eyzawiah Hassan (UPM Press, 2026)
Indexed by SCOPUS / MYCITE